Culture Shock: the legacy of the 1960s power generation schemes in Aotearoa New Zealand - Smith, Moira (Architectural History Aotearoa, 2022)
In 1960s Aotearoa New Zealand the response to a post war energy shortage was to look to the country’s rivers, lakes, and geothermal areas as a source of electric power. The Ministry of Works began a programme of dam building which peaked in the 1960s and made irreversible changes our lakes, rivers, and landscapes. Although New Zealand now produces about 80% of its electricity through renewable energy, the 1960s also saw a rise in environmental activism and a revaluing of the natural "wilderness." Professor John Salmon’s influential book, Heritage Destroyed: The Crisis in Scenery Preservation in New Zealand (1960), drew public attention to the environmental degradation caused by large-scale engineering projects, and the decade ended with the "Save Manapōuri" campaign which, in the early 1970s, prevented the raising of lakes Manapōuri and Te Anau to guarantee power to the Tiwai Point aluminium smelter. This paper considers the legacy of the 1960s power generation schemes, including changes to the physical landscape; new legislation for the preservation of the built and natural environments; and alternative ways to consider the cultural and natural landscapes that prioritise Te Mana o te Wai.